2019
DOI: 10.1109/access.2019.2913175
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Aware Algorithm for Virtual Machine Placement in Cloud Computing

Abstract: Virtualization technology, as a key technology in cloud computing, makes the virtual machine placement (VMP) play an important role in improving the energy efficiency of data centers. In this paper, an energy-aware algorithm named GATA is proposed for the VMP problem. It combines the genetic algorithm with the tabu search algorithm. The goal is to obtain an optimal VMP scheme to achieve energy efficiency while maximizing load balance among various resources. The algorithm is compared with two meta-heuristic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…An energy-efficient algorithm named GATA for VM allocation is designed by Zhao et al [25]. ey generated the proposed algorithm with a combination of genetic algorithm and tabu search algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…An energy-efficient algorithm named GATA for VM allocation is designed by Zhao et al [25]. ey generated the proposed algorithm with a combination of genetic algorithm and tabu search algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…While a study showed that a scalable network topology; flattened butterfly with commercial switch chips provides full utilization with reduced energy proportional datacenter [28]. Whereas, in [29], VM placement is addressed by combining two approaches that are genetic and the tabue search algorithms to reduce power consumption in cloud environment. Tabue search algorithm is used to enhance genetic algorithm searching by performing mutation operations.…”
Section: Sdn-based Cloud Computing Resource Management In Energy Effimentioning
confidence: 99%
“…The power consumption rate of hosts can be modeled as follows. The CPU energy consumption of a host and the utilization of the CPU can be expressed linearly [47], including three stages: idle, busy, and off. The energy consumption rate can be calculated as:…”
Section: Resource Allocation Modelmentioning
confidence: 99%